Z zagadnień estetyki językowej w komunikacji internetowej - na przykładzie kształtowania zachowań językowych w relacjach nadawca-odbiorca w blogu = The issues of language aesthetics in Internet communication - on the example of shaping language behaviors in the relation between the sender and the recipient on the blog - Półtorak, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is an attempt to analyze the category of language aesthetics in Internet communication. The aim of the detailed analysis is to show the principles of a specific linguistic etiquette used by the participants of the internet communication process. The basis of the analysis is an internet blog, characterized by high communication dynamics between the sender and the recipients.
Keywords: estetyka językowa; nadawca; odbiorca; blog; komunikacja internetowa; netykieta; language aesthetics; sender; recipient; Internet communication; netiquette